Redefining Industrial Maintenance Activity in the Modern Organization of Industrial Companies - Vasile DEAC; Gheorghe CÂRSTEA; Constantin BÂGU; Florea PÂRVU (Revista de Management Comparat International)
The maintenance activity isn’t a purpose in itself, it’s a necessity of which “the production suffers” and the financial agent “considers too expensive”. It often exists a conflict between the production units and the maintenance department, not only for a short term, but, sometimes, for a long term, imposing a rigorous definition of each person’s responsibilities. Considering the mutations in the industrial equipments’ technical complexity and the accidental failures’ catastrophic consequences from the economic and/or social point of view, it should be assigned a new dimension to the maintenance activity. One of the imperatives imposed to this action is represented by modern means of informing through the maintenance’s operational computerization.